Utilizing Garcinia indica Benzophenones as Natural Boosters for Enhanced Sunscreen Efficacy - Kadam, Janvi; Dike, Mamta; Pophali, Ketki; Dhawal, Pranjali; Deodhar, Manjushri (Contemporary Research and Perspectives in Biological Science Vol. 10, 2025)
The study focuses on exploring the UV absorption potential of natural benzophenones in Garcinia indica fruit rinds and assessing their effectiveness as SPF boosters in combination with commercial sunscreen actives. In our previous investigation, dried fruit rinds of Garcinia indica were extracted using ethyl acetate, and the extract was fractionated with water to yield a treated ethyl acetate fraction (TEAE). Thin-layer chromatography (TLC) and high-performance TLC mass spectrometry (HPTLC-MS) confirmed the presence of UV-absorbing benzophenones, demonstrating ultraviolet absorption properties of TEAE and the toxicity was ameliorated using kokum butter and algal polysaccharide. In the current study, n-hexane-ethyl acetate combinations were employed as solvents to extract phytocompounds of various polarities. The extracts were further evaluated and validated with previous studies for UV absorption spectra, in-vitro SPF, UVA boosting ability and cytotoxicity on dermal fibroblast cells. The extracts were shortlisted on the basis of the presence of hydroxycitric acid as confirmed with TLC and UV absorption spectra. The selected extracts were then incorporated into the cream formulations along with commercial sunscreen actives, octyl methoxycinnamate (OMC) and Uvinul A, and analyzed for photoprotective efficacy following COLIPA guidelines. From TLC analysis and UV-Vis analysis, it was concluded that increasing the ratio of ethyl acetate: n-hexane increased the SPF-associated properties due to phytocompounds like garcinol and benzophenones like 7-epi-iso-garcinol. The IC50 value on fibroblast cells was above 60 \(μ\)g/ml for all the extracts. TEAE showed the highest SPF (13.9) with 3% OMC but lacked a Boot Star rating. Incorporating 1% Uvinul A improved the formulation to SPF 9.38 with a Boot Star rating of 3. The findings support the potential of benzophenones extracted from Garcinia indica fruit rinds as natural SPF boosters. While previous studies addressed the cytotoxicity of TEAE in the formulation using adjuvants, this work highlights the natural benzophenone’s role in enhancing sunscreen through its UV-absorbing properties.